Digital Condylar Parameter Assessment Using Cadiax® 2 and Modjaw® - Smaranda Buduru; Sara Hafidi; Oana Almășan; Manuela Manziuc; Manuela Tăut; Rareș Buduru; Vlad-Ionuț Nechita; Andreea Kui; Andreea Chisnoiu; Cecilia Bacali (MDPI AG, 2024)
Background: The main aim of this research was to assess the reliability of two systems designed specifically for condylar movement recording using condylar slope and Bennett angle information. The objectives were to evaluate the validity of two subsequent null hypotheses: (1) there is no significant difference between the measurements of condylar slope and Bennett angle taken at T0 (initial) and T1 (after one week) using the same equipment; (2) there is no notable difference in the values of the condylar slope and Bennett angle measurements obtained using Modjaw and Cadiax 2. Methods: An observational, descriptive, and prospective study was conducted with a selected group of 25 individuals (13 females and 12 males) aged between 22 and 27. Results: The results of Cadiax 2 and Modjaw showed excellent measurement repeatability for both parameters, with intraclass correlation coefficients (ICC) above 0.90, indicating excellent reliability between T0 and T1, both at 3 mm and 5 mm of displacement. Modjaw had an overall average value relatively higher than Cadiax 2, even though Modjaw's condylar slope at 5mm had a significantly lower average value (37.4 ± 6.31) with an interval of 24.5-48.1, which was lower than Cadiax 2 (48.4 ± 10.6) with an interval of 30.5-68.5. Regarding the primary aim, it can be stated that both Modjaw and Cadiax 2 demonstrated excellent repeatability on their own, demonstrating robust reliability since there was no discernible difference between the T0 and T1 measurements. On the contrary, analyses of the two devices' measured values for the secondary aim showed a considerable difference. Conclusions: Even though each device is reliable on its own, the absolute values that are obtained are different. Technological differences between the systems may account for these variations.